2017
DOI: 10.1039/c7ra07095k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bacterial growth with the help of immiscible oxygenated oils

Abstract: Bacterial growth in an aqueous medium in the vicinity of the interface with an immiscible oxygenated fluid is a subject of this study. We tested six oxygenated liquids, including hexadecane, silicone oil, FC-40, FC-70, HFE-7200 and HFE-7500.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…For example, controlled carbon source supply in shake flasks has been achieved by controlled release of glucose by its diffusion from silicone beads or in situ degradation of polysaccharides . Oxygen availability can be modulated by proper flask design or by adding immiscible oxygenated oils . Lastly, devices that monitor these parameters and others have been adapted for cultures in microplates and shake flasks so that the best conditions for recombinant protein production can be found .…”
Section: Culture Conditions and Growth Monitoringmentioning
confidence: 99%
“…For example, controlled carbon source supply in shake flasks has been achieved by controlled release of glucose by its diffusion from silicone beads or in situ degradation of polysaccharides . Oxygen availability can be modulated by proper flask design or by adding immiscible oxygenated oils . Lastly, devices that monitor these parameters and others have been adapted for cultures in microplates and shake flasks so that the best conditions for recombinant protein production can be found .…”
Section: Culture Conditions and Growth Monitoringmentioning
confidence: 99%
“…In our case, roughly 1/3 of the volume of the chamber is filled by 2 nl droplets. Using the solubility coefficients of oxygen in complex medium 28 and in fluorocarbon oil, 29 we can calculate the amount of oxygen per droplet in the chamber. To estimate the oxygen consumption by bacteria inside a droplet, we assume that initially there is one bacterium inside the droplet which consumes oxygen with a rate 30 determined by the exponential growth of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was beneficial because the continuous phase was used as a carrier of oxygen or other substances needed to run the reactions inside droplets [ 43 ]. It was shown that the continuous phase of oxygenated oil amplified bacterial growth in the water phase [ 44 ]. In the presented loop-circulation, droplets had contact with fresh oil, which was continuously changing between containers and tubing.…”
Section: Resultsmentioning
confidence: 99%